2023
DOI: 10.3389/fnins.2023.1229307
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acute high-intensity interval training and Tabata training on inhibitory control and cortical activation in young adults

Xueyun Shao,
Longfei He,
Yangyang Liu
et al.

Abstract: IntroductionPhysical exercise not only benefits peoples’ health, but also improves their cognitive function. Although growing evidence suggests that high-intensity interval training (HIIT) is a time-efficient exercise regime that can improve inhibitory control performance by enhancing cortical activation in the prefrontal cortex, less is known about how Tabata training, a subset of HIIT that requires no equipment or facilities to perform, affects inhibitory control and cortical activation in young adults. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…consistent with these findings, an additional study reported impaired executive control in subjects who engaged in 30-minutes of endurance exercise at the ventilatory threshold compared to those who performed the same exercise at 75% of the ventilatory threshold [20]. However, recent studies have suggested that moderate intensity endurance exercise (between 64%-76% of maximal aerobic capacity) [21] and high intensity interval training [22] can improve acute cognitive function. A recent study by chen and colleagues [23] have reported significant acute improvements in executive functioning immediately following combined endurance and resistance training.…”
Section: Introductionmentioning
confidence: 70%
“…consistent with these findings, an additional study reported impaired executive control in subjects who engaged in 30-minutes of endurance exercise at the ventilatory threshold compared to those who performed the same exercise at 75% of the ventilatory threshold [20]. However, recent studies have suggested that moderate intensity endurance exercise (between 64%-76% of maximal aerobic capacity) [21] and high intensity interval training [22] can improve acute cognitive function. A recent study by chen and colleagues [23] have reported significant acute improvements in executive functioning immediately following combined endurance and resistance training.…”
Section: Introductionmentioning
confidence: 70%